Karstmorphologische, geologische und botanische Studien in der Sierra de los Organos auf Cuba - Lehmann, Herbert; Krömmelbein, Karl; Lötschert, Wilhelm (ERDKUNDE, 1956)
In the autumn of 1955 a research team from Frankfurt University carried out field investigations in the Sierra de los Organos, Cuba. Altogether an area of approximately 400 sq. Km. was mapped and investigated geomorphologically (by H. Lehmann), geologically (by K. Krömmelbein) and botanically (by W. Lötschert). In addition chemical research was pursued on karst corrosion processes under tropical conditions. The main object of the field ,investigations taken altogether was the study of the tropical type of karst and its genesis. The Sierra de los Organos, the Organ Pipe Range, forms a mountain chain in western Cuba stretching from La Palma to Guane. lt is of Laramic folding, and its highest parts, which hardly exceed 500 m., consist of Jurassic to Cretaceous and possibly also Eocene limestones and a series of sandstones and shales, the so-called Pizarras or Cayetano-formation. These latter, which occur on both sides of the limestone sierras, form a maturely dissected area of hills of an average altitude of 300 m., as for instance between the Anc6n and the Vifiales-InfernoChain; in part, however, this hill area is considerably lower. Contrary to Palmer (1945), the Cayetano formation is, because of its pre-Oxfordian age, to be considered older than the limestone in which, for the first time, fossils (Trigonia sp.) were found. Neither can Vermunt’s opinion be maintained that the limestone is embedded within the Cayetano formation. Tectonically the mountains show an ordinary imbrication structure in which the succession of strata - Cayetano formation, Jagua-formation (Upper Oxfordian), Vifiales limestone of Upper Jurassic to Cretaceous age - ,is repeated several times. The extent of the thrust faults is far smaller than was thought by Palmer; their dip is mainly northwards. The longitudinal and transversal faults are characterised by the occurrence of serpentinic masses which are frequently joined to and kneaded with layers of the Habana formation. The age of the imbrication is Post-Eocene or Late-Eocene; the Eocene Strata which have been affected tectonically and which superimpose normally the unstratified limestone of Cretaceous age still require a more exact stratigraphical classification. As regards the morphology, the existing relief originated from an arch whose axis nearly coincides with the present watershed. The highest hills, however, the limestone sierr:1s, are located north of this axis in the northern part of the arch. The results of the geomorphological research showed that three different levels were formed in the course of erosion and denudation. The oldest may be consider d comparable to the Upper Miocene peneplain of other parcs of Cuba. lt corresponds with the level of the plateau-like limestone sierras taken as a whole, which are dissected into single limestone cones. A considerably lower level cuts the steeply dipping Pizarras and part of the limestone rocks. A third level is formed by plains and enclosed basins which surround the limestone sierras. Individually the limestone sierras show eh e typical Kegelkarstrelief of rounded cones and chimney like sinkholes or Yamas. Their sur face is completely covered by pointed lapies (Karren). Those beds which consist of other than the Upper Oxfordian pure limescone show no tendency towards formation of Kegelkarst, though they too display karsttopography. lt is a new observation that basins and plains, for which I suggest the name Randpolien (marginal poljes), without surface drainage, have formed around the limestone sierras. They all show the features of a poljie. They are surrounded by higher ground, are without surface drainage, have a fairly flat bottom, but are bordered on one side by insoluble rocks (Pizarras) . As is shown by isolated limestone covers (Mogocen) which rise above the polje bottoms, these marginal poljes (Randpolien) have expanded into the limestone from the boundary between the limestone and the shale. The drainage of these poljes takes place subterraneously through the limestone mountains. Evidently detritus of insoluble matter is also carried away subterraneously since sand and gravel of shale and serpentine occur at the mouths of cavernous rivers. In chose cases where surface drainage is found, I suggest the adoption of the term Karst margin plains (Karstrandebenen) as understood by K. Kayser, since these plains are mostly situated still within the limestone area. Both marginal poljes and karst margin plains always lie deeper than the neighbouring shale area and lie considerably deeper than the limestone sierras which rise out of them with steep cliffs of often more than 100m in height. In addition the genuine poljes completely surrounded by limestone are also found (Jaruko Hoye, Portreico Hoye, etc ). The development of the poljes, marginal poljes and karst margin plains is a result of undermining by karst corrosion as described by H. Lehmann elsewhere. The level of their bottoms depends on the level of the Vorfluter, i.e. the surface stream , into which they are being drained and which form a local base level. The karst formation process advanced under tropical conditions at considerable speed . Although the warm tropical rainwater contains only small quantities of C02 (2.5-3.5 milligrams per litre) a great quantity of C02 is brought into the ooze water and the water running down the lapies (Karren) by the carbon dioxide which becomes available through the respiration of the microorganisms of the endolothic limestone rows (Verrucaria sp.) and the macro vegetation. Our analysis showed that water which had been running down on limestone for only a short distance already contained up to 21mg of free C02 per litre. Consequently the corrosion effect is unusually great; analyses of water trickling down limestone showed up to 157 mg CaCO3 per litre. These quantities are considerably greater than those measured in Europe. As regards the vegetation in the area of the Sierra de los Organos, according to the different ecological conditions three types of woods have developed. The xerophytic vegetation of the limestone is characterised by the joint occurrence of Spathelia brittonii, Bombax emarginata and Carissia princeps. The hilly Pizarras are covered with dry oak woods (with Quercus virginiana) and in the higher parts with woods of Pinus tropicalis and Pinus carribbea. Both oaks and pines form a mesophytic mixed forest.